A Biomechanical and Microstructural Analysis of Bovine and Porcine Pericardium for Use in Bioprosthetic Heart Valves. Issue 5 (3rd September 2021) - Campion, Greg; Hershberger, Kylie; Whelan, Alix; Conroy, Jack; Lally, Caitríona; Murphy, Bruce P.
ABSTRACT: Background: Animal-derived pericardium is a key material that enables the successful clinical use of bioprosthetic heart valves. Recently, transcatheter heart valves have placed more emphasis on the enhancement of this tissue, especially in terms of producing a uniform, thin, durable tissue. In this study, we provide a new method to achieve thinner tissue and new insights into how to achieve a more consistent tissue, which potentially may lead to more durable heart valves. Methods: We compared four groups of tissue: porcine pericardium, bovine pericardium; delaminated serous bovine pericardium, and delaminated fibrous bovine pericardium. The properties we compared were: surface characteristics, collagen fiber alignment, collagen fiber alignment patterns, and tensile mechanical properties. Results: We produced thinner tissue that had statistically significantly reduced surface roughness and was not mechanically inferior. Furthermore, we demonstrated that porcine tissue has more distinct collagen fiber directions between the fibrous and serous sides. The maximum observed difference in average fiber angles between the different sides of porcine tissue was 52.3° (±25.9°) and 33.4° (±27.1°) for bovine tissue, this was statistically significantly different. Conclusion: The results indicate that screening heart valve leaflet pericardial tissue to identify optimally aligned collagen fiber directions is not viable. We propose an alternative approach: utilizing tissue with eccentricity values below a threshold value of 0.65 and discarding tissue with eccentricity values above 0.65. If screening procedures are not available, our results suggest that non-screened porcine pericardial tissue would produce more consistent mechanical properties, as areas with aligned collagen fibers are not consistently present in porcine tissue.